On statistical parameters characterizing vibrations of damped oscillator forced by stochastic impulses - M. Jabłoński; A. Ozga (Archives of Acoustics)
Our theoretical study aims at finding some statistic parameters characterizing the vibrations of an oscillator with damping and forced by stochastic impulses. We will derive the dependence of these parameters on rigidity and mass of the oscillator and on the stochastic distribution of the impulse magnitude.We will also carry out a numerical simulation verifying the derived mathematical model and interpret the differences between the results obtained in simulation and the mathematical calculations. This study is the first stage of research aimed at designing a probe that will facilitate measuring parameters determining the quality of a technological process.